A Dystopian Climate for Transitional Justice: Naming Recent Violence in Medellín. (September 2016) - Phillips-Amos, Georgia
As Colombia's asymmetric war has evolved, gravitating toward cities, it has become absorbed by a transitional justice system. In the process, language used to name relevant stakeholders, shape national narratives of collective memory, and activate legal infrastructure is mediated by a symbolic and often duplicitous system of governance. A history of political violence and attempts to impose security focusing on the contemporary population of Comuna 13, the fastest-growing site of urban displacement in the city of Medellín, gives context to stories of violence that are otherwise eclipsed by the process of collective memory making and describes grassroots attempts at retracing a public narrative. Mientras la guerra asimétrica en Colombia ha ido evolucionado, gravitando más y más hacia las ciudades, ésta ha sido absorbida por un sistema de justicia transicional. En este proceso, el lenguaje que se utiliza para nombrar a los actores más importantes, construir narrativas nacionales sobre la memoria colectiva y activar una infraestructura legal está condicionado por un sistema de gobernanza simbólico y a menudo engañoso. La historia sobre la violencia política y los esfuerzos por imponer medidas de seguridad en la Comuna 13—la zona de desplazamiento urbano de más alto crecimiento en la ciudad de Medellín— le da un contexto a las historias de violencia que de otra manera serían eclipsadas por el proceso de construir la memoria colectiva y describe los esfuerzos de base para recrear una narrativa pública.